A nanocarrier containing carboxylic and histamine groups with dual action: acetylcholine hydrolysis and antidote atropine delivery - Mansurova, Elina E.; Maslennikov, Andrey A.; Lyubina, Anna P.; Voloshina, Alexandra D.; Nizameev, Irek R.; Kadirov, Marsil K.; Mikhailova, Anzhela A.; Mikshina, Polina V.; Ziganshina, Albina Y.; Antipin, Igor S. (Beilstein Journal of Nanotechnology, 2025)
Disruption of cholinesterases and, as a consequence, increased levels of acetylcholine lead to serious disturbances in the functioning of the nervous system, including death. The need for rapid administration of an antidote to restore esterase activity is critical, but practical implementation of this is often difficult. One promising solution may be the development of antidote delivery systems that will release the drug only when acetylcholine levels are elevated. This approach will ensure timely delivery of the antidote and minimize side effects associated with uncontrolled drug release. Here, we describe the creation of a new smart system that serves as a carrier for delivering an antidote (i.e., atropine) and functions as a synthetic esterase to hydrolyze acetylcholine. The nanocarrier was synthesized through microemulsion polycondensation of phenylboronic acid with resorcinarenes containing hydroxy, imidazole, and carboxylic groups on the upper rim. The nanocarrier breaks down acetylcholine into choline and acetic acid. The latter acts on the boronate bonds, dissociating them. This leads to the destruction of the nanocarrier and the release of the antidote. The paper covers the creation of the nanocarrier, its physicochemical and biological properties, encapsulation of the antidote, acetylcholine hydrolysis, and antidote release.
Keywords: acetylcholine; antidote delivery; artificial cholinesterase; atropine; nanocarrier; resorcinarene